An exploratory study of advancing interdisciplinary research trends in digital new media - HSIN-PEY PENG (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The paper’s overarching goal is to provide a theoretical framework for analyzing modern platform-based media ecosystems, and it does so by discussing three theoretical stances that offer promising new avenues of inquiry within the larger framework of communication studies. The paper zeroes in on how the original two ends of the communication process, the communicators and the receivers, change as a result of technology-centred contributions to social impact.Method: The two primary aspects of the methodology are discussed in this paper, and they are illustrated with examples using a logical research path and path diagram. An investigation into potential interdisciplinary research developments in digital new media will use existing literature reviews and theoretical perspectives on their application across disciplines as its primary framework.Findings: People’s knowledge of and care about how they use media can be strengthened by interdisciplinary research in new media, which examines the fundamental shift in medium and the communication capabilities derived from new media. This helps advance the field of digital new media research, which fosters investigation into novel forms of communication and the study of its interdisciplinary practices, and further enriches and develops the theory of communication in the twenty-first century.Implications/Novel Contribution: By allowing anyone to contribute, UGC gives people who use new media a chance to act as content creators, agents, and practitioners all at once. As a result of this trend, substantial social transformations will be accelerated and amplified. As a result, new media cannot be viewed as merely a new-style communication instrument but as a fusion of several different disciplinary dimensions. The data was collected to bolster foreseeable interdisciplinary social sciences and humanities progress.